Efficient capture of low partial pressure H2S by tetraethyl ammonium amino acid ionic liquids with absorption-promoted solvents. Issue 103 (25th October 2016) - Wang, Bing; Zhang, Kai; Ren, Shuhang; Hou, Yucui; Wu, Weize
Abstract : Ethylene glycol can enhance the absorption capacity of H2 S in ILs. Abstract : To capture H2 S from gas mixtures, ionic liquids (ILs), especially functional ILs, are regarded as novel absorbents and can absorb a large amount of H2 S at high pressures. However, the solubility of dilute H2 S in functional ILs is still very low and the viscosities of H2 S-absorbed ILs are very high resulting in long absorption equilibrium times. To enhance the solubility and reduce the equilibrium time, we designed mixtures of functional ILs, tetraethyl ammonium amino acids, and ethylene glycol (EG) to capture dilute H2 S of 0.005 MPa. It has been found that these mixtures can absorb a large amount of H2 S from mixed gas, and EG content, temperature, H2 S mole fraction and type of ILs have significant influence on the absorption. At 40 °C, the solubility of H2 S in the mixture can reach up to 2.36 mol H2 S per kg mixture. EG in the ILs mixtures not only decreases the viscosity of ILs before and after the absorption, but also enhance the absorption capacity of H2 S in ILs. Low temperatures, high H2 S partial pressures and low p K b of –NH2 (or –NH) in amino acids formed the anion of ILs have positive effects on H2 S absorption in the mixtures. The mechanism of H2 S absorption by functional IL and EG mixtures has also been proposed.